2012
DOI: 10.1128/jcm.06372-11
|View full text |Cite
|
Sign up to set email alerts
|

Scalp Abscess Due to Streptomyces cacaoi subsp. cacaoi , First Report in a Human Infection

Abstract: Streptomyces cacaoi subsp. cacaoi, a Gram-positive, branching filamentous bacteria, was isolated from a scalp infection in a patient from Pondicherry, India. Phenotypic tests identified the isolate as a Streptomyces species, but 16S rRNA sequence analysis provided the species identification required for tracking of this emerging pathogen. CASE REPORTA 31-year-old female patient presented to medical care at Aarupadai Veedu

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
7
1
1
Order By: Relevance
“…Another study done on Gordonia by Moser et al, [21] showed susceptibility to Ceftriaxone, Clarithromycin, Linezolid, Amikacin, Amoxicillin-Clavulanate and Ciprofloxacin. Resistance to Ceftriaxone was observed on a study done on Streptomyces [22] which is on the contrary to the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…Another study done on Gordonia by Moser et al, [21] showed susceptibility to Ceftriaxone, Clarithromycin, Linezolid, Amikacin, Amoxicillin-Clavulanate and Ciprofloxacin. Resistance to Ceftriaxone was observed on a study done on Streptomyces [22] which is on the contrary to the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…cacaoiAB184115 was isolated for the first time in 1932 by Waksman from cacao beans, and then Streptomyces cacaoi strain SU2 JF730119 from marine sediment (Nandhini and Selvam, 2011) and Streptomyces cacaoi subsp. cacaoi strain GU144523 from scalp (Pellegrini, 2012). This is the first record of Streptomyces cacaoi to be isolated from Egyptian soil by selective pretreatments on humic acid vitamin agar media with this comprehensive study of antimicrobial activity, phylogenetic analysis and chemical characteristic of antibiotics components.…”
Section: Minimum Inhibitory Concentration (Mic) Of Bioactive Fractionmentioning
confidence: 99%
“…However, it was resistant to trimethoprim-sulfamethoxazole (cotrimoxazole, COX), showing completely no inhibition zone. This is not so often among streptomycetes, being previously observed only in streptomycete isolate from lung nodule (Kapadia et al, 2007), in Streptomyces cacaoi isolated from scalp abscess (Pellegrini et al, 2012), and in 29% of clinical streptomycete isolates of the study of McNeil (McNeil et al, 1990). Interestingly, the patient had been treated with COX a few years prior to the strain isolation.…”
Section: Discussionmentioning
confidence: 85%